Pharmacological enhancement of slow-wave activity at an early disease stage improves cognition and reduces amyloid pathology in a mouse model of Alzheimer’s disease - Sedef Kollarik; Sedef Kollarik; Sedef Kollarik; Dorita Bimbiryte; Aakriti Sethi; Inês Dias; Inês Dias; Inês Dias; Carlos G. Moreira; Daniela Noain; Daniela Noain; Daniela Noain; et al. (Frontiers in Aging Neuroscience)
IntroductionImproving sleep in murine Alzheimer’s disease (AD) is associated with reduced brain amyloidosis. However, the window of opportunity for successful sleep-targeted interventions, regarding the reduction in pathological hallmarks and related cognitive performance, remains poorly characterized.MethodsHere, we enhanced slow-wave activity (SWA) during sleep via sodium oxybate (SO) oral administration for 2 weeks at early (6 months old) or moderately late (11 months old) disease stages in Tg2576 mice and evaluated resulting neuropathology and behavioral performance.ResultsWe observed that the cognitive performance of 6-month-old Tg2576 mice significantly improved upon SO treatment, whereas no change was observed in 11-month-old mice. Histochemical assessment of amyloid plaques demonstrated that SO-treated 11-month-old Tg2576 mice had significantly less plaque burden than placebo-treated ones, whereas ELISA of insoluble protein fractions from brains of 6-month-old Tg2576 mice indicated lower Aβ-42/Aβ-40 ratio in SO-treated group vs. placebo-treated controls.DiscussionAltogether, our results suggest that SWA-dependent reduction in brain amyloidosis leads to alleviated behavioral impairment in Tg2576 mice only if administered early in the disease course, potentially highlighting the key importance of early sleep-based interventions in clinical cohorts.